2022
DOI: 10.3389/fnhum.2022.806047
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Children’s Self-Reports of Attention Deficit Hyperactivity Disorder-Related Symptoms and Their Associations With Subjective and Objective Measures of Attention Deficit Hyperactivity Disorder

Abstract: BackgroundThe diagnosis of Attention deficit hyperactivity disorder (ADHD) is primarily dependent on parents’ and teachers’ reports, while children’s own perspectives on their difficulties and strengths are often overlooked.GoalTo further increase our insight into children’s ability to reliably report about their ADHD-related symptoms, the current study examined the associations between children’s self-reports, parents’ and teachers’ reports, and standardized continuous performance test (CPT) data. We also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It is also indicative that for children and adolescents with ADHD, values for QbTest variables could provide additional clinical information to be used for the treatment tailoring or following up the course once ADHD is diagnosed, which has been prospectively documented (e.g., Cedergren et al, 2022; (Knez et al, 2021; Stevanovic et al, 2022). Especially, the QbTest in clinical use may provide more theoretical, construct-based measures of inattention than parental ratings, in which hyperactivity and inattention seem to mingle substantially (Hamadache et al, 2021), or children’s self-reports, in which inattention and CPT show minimal association (Slobodin & Davidovitch, 2022). Thus, the added value of the QbTest, beyond a classical CPT, lies in the activity component and data for hyperactivity (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is also indicative that for children and adolescents with ADHD, values for QbTest variables could provide additional clinical information to be used for the treatment tailoring or following up the course once ADHD is diagnosed, which has been prospectively documented (e.g., Cedergren et al, 2022; (Knez et al, 2021; Stevanovic et al, 2022). Especially, the QbTest in clinical use may provide more theoretical, construct-based measures of inattention than parental ratings, in which hyperactivity and inattention seem to mingle substantially (Hamadache et al, 2021), or children’s self-reports, in which inattention and CPT show minimal association (Slobodin & Davidovitch, 2022). Thus, the added value of the QbTest, beyond a classical CPT, lies in the activity component and data for hyperactivity (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other works (Achenbach, 2006; De Los Reyes & Kazdin, 2005) have demonstrated that self‐reports offer valuable information across a broader spectrum of psychiatric disorders. Moreover, a recent study by Slobodin and Davidovitch (2022) found that self‐rating scores provide informative data in relation to both teacher and parent reports, as well as objective measures of attention. Hence, there arises a need to explore implicit biases not only in the rating scores provided by parents and teachers but also in self‐reports.…”
Section: Introductionmentioning
confidence: 99%
“…A 504 and IEP are formal plans schools develop to remove learning barriers for children with learning disabilities or deficiencies so they can access the curriculum. Unfortunately, children’s behavioral patterns are often misdiagnosed as hyperactive and inattentive then subsequently medicated when they are simply sleep deprived or exhibiting a form a normal developmental pattern (Center for Disease Control and Prevention, n.d.b; Slobodin & Davidovitch, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of breathing disorders at sleep impacts 15% of children due to variations in the upper airway, while 90% will go undiagnosed as adults (Gokdemir et al, 2021). The relationship between SDB and ADHD has been proposed yet remains controversial in a scenario of which came first (Gokdemir et al, 2021; Slobodin & Davidovitch, 2022; Tsukada et al, 2018; Urbano et al, 2021; Wu et al, 2017). While adults may feel fatigued from sleep deprivation, it’s not uncommon for sleep-deprived children to become hyperactive; another reason is that a child may be misdiagnosed with ADHD instead of sleep apnea (Javaheri & Javaheri, 2020; Knight & Dimitriou, 2019; Tan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%